First, expand the terms in parenthesis by multiplying each term within the parenthesis by the term outside the parenthesis:
sqrt( color(red)(7) ) ( sqrt(color(blue)(14)) + sqrt(color(blue)(3)) ) =>
(sqrt(color(red)(7)) xx sqrt(color(blue)(14))) + (sqrt(color(red)(7)) xx sqrt(color(blue)(3)))
Next, we can use this rule for radicals to rewrite the expression:
sqrt(color(red)(a)) * sqrt(color(blue)(b)) = sqrt(color(red)(a) * color(blue)(b))
sqrt(color(red)(7) xx color(blue)(14)) + sqrt(color(red)(7) xx color(blue)(3)) =>
sqrt(98) + sqrt(21)
We can rewrite the term on the left as:
sqrt(49 xx 2) + sqrt(21)
We can use the reverse of the rule above to simplify the term on the left:
sqrt(color(red)(a) * color(blue)(b)) = sqrt(color(red)(a)) * sqrt(color(blue)(b))
sqrt(color(red)(49) xx color(blue)(2)) + sqrt(21) =>
(sqrt(color(red)(49)) xx sqrt(color(blue)(2))) + sqrt(21) =>
(7 xx sqrt(color(blue)(2))) + sqrt(21) =>
7sqrt(color(blue)(2)) + sqrt(21)